Potential Assessment of E-Waste Plastic in Metakaolin Based Geopolymer Using Petrography Image Analysis - Parth Verma; Priyanka Dhurvey; Venkatesa Prabhu Sundramurthy (Advances in Materials Science and Engineering)
Concrete’s binder can be substituted with rice husk ash, metakaolin, kaolin clay, GGBS, and other agricultural and industrial byproducts and waste materials, which lowers greenhouse gas emissions, namely carbon dioxide (CO2). When employed in the manufacturing of concrete, the aforementioned items reduce the amount of water required and have no discernible impact on the material’s long-term performance. Combination of metakaolin and class-F fly ash is taken for this experimental study to create geopolymer concrete, as both the materials are very good sources of alumino-silicates, which is the foremost requirement for the material to be the binder in geopolymer concrete. Also, the percentage replacement of crushed aggregates with crushed E-waste plastic (EWP) is are created for making the concrete eco-friendlier as the EWP is a big problem for us to dispose of it. To activate raw ingredients and mixing of concrete, alkaline solution is used, made from sodium hydroxide (NaOH) and water glass solution, i.e., sodium silicate (Na2SiO3). Low molarity metakaolin geopolymer concrete (MGPC) was created to have benefits over standard cement concrete in terms of performance, durability, and mechanical properties. This study describes the findings of a comprehensive experimental test and analysis to investigate the characteristics of MGPC-EWP with a change in different factors of the mix design. The study’s findings demonstrated that MGPC performance is closely correlated with its molarity, as the molarity increases, the mechanical strengths of the MGPC also increases. Also, the optimum percentages of the EWP are to be incorporated in the MGPC. This study also uses the petrographic image analysis to validate the geopolymerization products forms in the MGPC and check the microstructure growth of geopolymerization of particles with age. The petrographic image analysis provides photographs of the microstructure of hydration products of the samples with good details. As the petrographic microscope is very affordable as compared to the SEM setup and requires less skilled worker, it comes out to be a good approach for the microstructural analysis.